Initiating Children into Hermeneutical Discourses in Religious Education: A Response to Rachel Cope and Julian Stern - Freathy, Rob (Journal for the Study of Spirituality, 2013)
In response to previous articles in this journal by Rachel Cope and Julian Stern, and using an example of classroom practice, this article promotes a form of multi-faith religious education in which primary-school pupils (age 5-11) are re-conceived as joint researchers working alongside their teachers, through processes of imaginative and empathetic dialogue, to investigate the effectiveness of different methodologies and methods of studying religion(s). This pedagogical strategy seeks to teach pupils the disciplinary knowledge and skills associated with the communities of academic practice concerned with theological and religious studies, and more specifically to initiate them into the hermeneutical discourses which underlie theological and religious research and teaching. Moreover, it is argued that some of the suggested practices could be applied to the study of spirituality in any context and could contribute to the spiritual development of participants.